ANALYSIS OF HEALTH LEVEL, SHARIA MAQASHID INDEX AND POTENTIAL FINANCIAL DISTRESS AT BANK MUAMALAT INDONESIA FOR THE 2017- 2020 PERIOD - Mohammad Khoiruzi Afiq; Ana Toni Roby Candra Yudha (Universitas Airlangga, 2023)
This study aims to comprehensively measure the performance of Bank Muamalat Indonesia as the oldest Islamic bank in Indonesia that has experience in facing the 1998 monetary crisis, which is very interesting as a research object. This research uses a comparative descriptive method with a quantitative approach. The data used is of the time series data type in the form of BMI's financial statements for the 2017-2020 period. The analytical techniques used in this study used several techniques and stages, namely the level of bank health using the RGEC method, the achievement of sharia maqashid using Abu Zahrah's version of the sharia maqashid index, comparison of RGEC and IMS performance using quadrant analysis measurement (QAM) and analysis of potential financial distress using Zmijewski (X-Score). The results show that the use of the RGEC and IMS methods at Bank Muamalat Indonesia can complement the advantages and disadvantages of each performance measuring instrument. Meanwhile, the performance results from the analysis of potential financial distress through the Zmijewski method (X-score) have provided validation and strengthened the performance results of the RGEC and IMS. This study recommends that the management of Bank Muamalat Indonesia increase the amount of financing by prioritizing the principle of prudence, considering that a suitable risk profile and capital performance should be able to overcome earnings performance that is not optimal. In addition, advice to Bank Indonesia to review Bank Indonesia regulatory policy No.13/1/PBI/2011 related to the use of the RGEC method as an assessment of bank health levels wherein the performance assessment policy does not have a specific specialization for performance assessment of Islamic banks.